2003
DOI: 10.1080/j.1600-0455.2003.00088.x
|View full text |Cite
|
Sign up to set email alerts
|

Camurati-engelmann disease: Review of radioclinical features

Abstract: The most frequent symptoms were pain and muscle weakness accompanied by waddling gait. Two patients were asymptomatic. Radiologically, the disease can be classified as a craniotubular hyperostosis. Typically, fusiform thickening of the diaphyseal portions of the long bones was seen in all 8 patients, but in 1 patient, metaphyseal involvement was observed as well. Radioclinical abnormalities were most often detected before the age of 30, and were usually more extensive at older age. Radiological abnormalities m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 6 publications
(14 reference statements)
0
22
1
2
Order By: Relevance
“…Devido a isso, alguns autores especulam a possibilidade de existirem duas formas de DDP, uma pura, na qual apenas a ossificação intramembranosa é afetada, e outra mista, na qual também há um componente endocondral (1) . A sua fisiopatologia ainda não é totalmente compreendida, no entanto, as alterações patológicas parecem ser causadas da doença varia de 3 meses até 50 anos de idade (2) . Os sintomas mais freqüentemente encontrados são dores nos membros inferiores, fraqueza muscular e marcha cambaleante.…”
Section: Introductionunclassified
“…Devido a isso, alguns autores especulam a possibilidade de existirem duas formas de DDP, uma pura, na qual apenas a ossificação intramembranosa é afetada, e outra mista, na qual também há um componente endocondral (1) . A sua fisiopatologia ainda não é totalmente compreendida, no entanto, as alterações patológicas parecem ser causadas da doença varia de 3 meses até 50 anos de idade (2) . Os sintomas mais freqüentemente encontrados são dores nos membros inferiores, fraqueza muscular e marcha cambaleante.…”
Section: Introductionunclassified
“…These patients may present with increased fatigability (due to narrowing of the medullary cavity), as well as leg pain and a waddling gait (due to sclerotic expansion of diaphyseal segments), in the setting of normal laboratory studies [4]. The definitive diagnosis is made on the basis of radiographic findings: fusiform cortical thickening in the diaphyseal portions of tubular bones, occurring in a symmetrical distribution [30]. Although sporadic cases have been described, patients usually have a positive family history.…”
Section: Discussion and Treatmentmentioning
confidence: 99%
“…Camurati-Engelmann disease, also known as progressive diaphyseal dysplasia, is a rare autosomal dominant disorder of intramembranous ossification [4,30]. The pathophysiology of this disease process is based in aberrant endosteal and periosteal bone formation, producing hyperostosis of the cranial and tubular bones [4].…”
Section: Discussion and Treatmentmentioning
confidence: 99%
“…However, absence of mutations in the coding region of TGF-ß1 was described, indicating the existence of at least one other form 14 . Based on the existence of mutation in the TGF-ß1 or exclusion of the TGF-ß1 gene as the site of mutation, CED is classified as type I 15 or type II 14 , respectively.Bone pain in the extremities was reported to be the most common clinical symptom (68%); other important features were waddling gait (48%), easy fatigability (44%), and generalized muscle weakness (39%), or an asymptomatic presentation 5,6 . Campos-Xavier, et al 10 found no obvious The radiological changes include symmetrical endosteal and subperiosteal cortical thickening, and involve primarily the diaphyses, and may extend to the metaphysis but spare the epiphyses 5,6 .…”
mentioning
confidence: 99%
“…The disease begins in an age span between 3 months and 50 years old, with higher prevalence in males. It is characterized by progressive cortical expansion, sclerosis, and symmetrical hyperostosis affecting the diaphyses of the long bones 4,5 . We describe a case of CED in a female patient with lower limb pain with progressive worsening and difficult diagnosis.…”
mentioning
confidence: 99%